Role of Education in Financial Inclusion of Poor and Unbanked Women in India - Amra Sabic-El-Rayess (Universitas Muhammadiyah Surakarta, 2019)
In recent times, the global financial system has embraced more people from more regions of the world, but we are yet to fully understand who remains excluded and why. Globally, 2 billion adults are still unbanked (World Bank, 2015). Of those, many are poor women. Even when they gain financial access, women tend to refrain from actively using their bank accounts. India represents a potent example of this global challenge. Our study offers a quantitative analysis of the Financial Insights Inclusion and Findex datasets and finds that even when they are given the opportunity and potential benefits of financial access - many of India’s poor women opt out of actively engaging with the formal banking institutions. In examining reasons behind their account dormancy, we find that education is a significant determinant shaping decisions of India’s poor women.